Topical application of the ethanol extract and the hydroethanolic fraction of ripe Solanum lycocarpum A. St. Hil. fruit improves the healing of excisional wounds - Elisângela Elduina Ferreira; Renan Diniz Ferreira; Milena Santos de Almeida; Renan Araújo Costa; Izabela Caputo Assis Silva; Melissa Grazielle Morais; Karen Helaine Mendes Bertolin; Paula Vieira Teixeira Vidigal; Raquel Alves Costa; Luciana Alves Rodrigues dos Santos Lima; Flávia Carmo Horta Pinto (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To evaluate the effect of the topical application of the ethanol extract (EESL) and the hydroethanolic fraction (HFSL) of ripe Solanum lycocarpum fruit on the healing of experimentally-induced wounds in mice. Methods: The EESL and HFSL obtained from ripe fruit of the species S. lycocarpum were obtained by percolation with ethanol. They were tested in the healing of excisional wounds in mice, which were induced in anesthetized animals using a 7-mm dermatological punch. They were divided according to the treatment period and group, n = 6, and received topical application of the EESL or HFSL daily or saline solution for one, five, seven, or 21 days. At the end of this period, the animals were euthanized, and the lesions were subjected to histopathological processing and analysis to evaluate macroscopic area of the wound and microscopic analysis by morphometry of the number of leukocytes, mast cells, fibroblasts, re-epithelialization, and matrix deposition. Results: The application of the EESL and HFSL reduced the number of leukocytes after one, five, and seven days of treatment. EESL improved re-epithelialization and tissue proliferation in wound healing from day 7. Conclusion: The study demonstrated that daily administration of EESL and HFSL exhibit wound healing activity, with this effect being more pronounced by EESL. To our knowledge, this is the first report of the anti-inflammatory and healing activity of this species through topical application.